Discrete optimizations’ problems of deliveries of heterogeneous products - V. V. Egorov (Вестник университета, 2023)
The article touches upon issues related to the tasks of the national project «Smart City». The paper analyzes the problem of supplying a conditional consumer with heterogeneous products in accordance with his demand for deliveries from several suppliers in a situation with fixed surcharges, in addition to the cost of purchasing each unit of production. For the situation under study, a model of a reduced transport type with a discontinuous piecewise linear objective function of minimized total costs and with a system of linear constraints is constructed. A method for finding the optimal solution one of the many such solutions, based on the ideas of the Hungarian algorithm is proposed, the justification of which is given on the basis of the corresponding lemma. A refinement of the method is presented in the presence of some restrictions related to suppliers. The polynomial complexity of the method, i.e. the problem is quickly solvable, and the significant limitation of the applicability of the method within the framework of the model are noted. Further possible research directions of a stochastic or fuzzy nature are indicated.